Biofortified and fortified maize consumption reduces prevalence of low milk retinol, but does not increase vitamin A stores of breastfeeding Zambian infants with adequate reserves: a randomized controlled trial. Issue 5 (10th March 2021) - Palmer, Amanda C; Jobarteh, Modou L; Chipili, Mackford; Greene, Matthew D; Oxley, Anthony; Lietz, Georg; Mwanza, Rose; Haskell, Marjorie J
ABSTRACT: Background: Replacement of conventional staples with biofortified or industrially fortified staples in household diets may increase maternal breast milk retinol content and vitamin A intakes from complementary foods, improving infant total body stores (TBS) of vitamin A. Objectives: To determine whether biofortified or industrially fortified maize consumption by Zambian women and their breastfeeding infants could improve milk retinol concentration and infant TBS. Methods: We randomly assigned 255 lactating women and their 9-mo-old infants to a 90-d intervention providing 0 µg retinol equivalents (RE)/d as conventional maize or ∼315 µg RE/d to mothers and ∼55 µg RE/d to infants as provitamin A carotenoid-biofortified maize or retinyl palmitate–fortified maize. Outcomes were TBS, measured by retinol isotope dilution in infants (primary), and breast milk retinol, measured by HPLC in women (secondary). Results: The intervention groups were comparable at baseline. Loss to follow-up was 10% ( n = 230 mother-infant pairs). Women consumed 92% of the intended 287 g/d and infants consumed 82% of the intended 50 g/d maize. The baseline geometric mean (GM) milk retinol concentration was 1.57 μmol/L (95% CI: 1.45, 1.69 μmol/L), and 24% of women had milk retinol <1.05 μmol/L. While mean milk retinol did not change in the biofortified arm (β: 0.11; 95% CI: −0.02, 0.24), the intervention reduced low milk retinol (RR: 0.42; 95% CI: 0.21, 0.85). Fortified maize increased mean milk retinol (β: 0.17; 95% CI: 0.04, 0.30) and reduced the prevalence of low milk retinol (RR: 0.46; 95% CI: 0.25, 0.82). The baseline GM TBS was 178 μmol (95% CI: 166, 191 μmol). This increased by 24 µmol (± 136) over the 90-d intervention period, irrespective of treatment group. Conclusions: Both biofortified and fortified maize consumption improved milk retinol concentration. This did not translate into greater infant TBS, most likely due to adequate TBS at baseline. This trial was registered at clinicaltrials.gov as NCT02804490.